2013
DOI: 10.1186/1477-7819-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glioma-associated oncogene 2 (Gli 2) is correlated with poor prognosis in patients with hepatocellular carcinoma undergoing hepatectomy

Abstract: BackgroundOur previous studies showed that glioma-associated oncogene (Gli)2 plays an important role in the proliferation and apoptosis resistance of hepatocellular carcinoma (HCC) cells. The aim of this study was to explore the clinical significance of Gli2 expression in HCC.MethodsExpression of Gli2 protein was detected in samples from 68 paired HCC samples, the corresponding paraneoplastic liver tissues, and 20 normal liver tissues using immunohistochemistry. Correlation of the immunohistochemistry results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
(32 reference statements)
4
28
1
Order By: Relevance
“…As in our study, the dysregulated HH signaling is often mirrored by increased expression of downstream transcription factors GLI (18,19). In line with our data, a negative prognostic impact of GLI2 expression was very recently shown for gastric, hepatocellular and oral squamous cell cancer (20)(21)(22).…”
Section: Discussionsupporting
confidence: 77%
“…As in our study, the dysregulated HH signaling is often mirrored by increased expression of downstream transcription factors GLI (18,19). In line with our data, a negative prognostic impact of GLI2 expression was very recently shown for gastric, hepatocellular and oral squamous cell cancer (20)(21)(22).…”
Section: Discussionsupporting
confidence: 77%
“…In transitional cell carcinoma cell lines, overexpression of GLI2 increases the invasive nature of these cells in Matrigel invasion assays [62] . GLI2 expression had been known to be increased in hepatocellular carcinoma when compared to nearby normal liver, but it was also determined that this increase in expression correlated with intrahepatic metastasis and vascular invasion [74] . Lending further explanation to this finding, immunohistochemistry of these tumors revealed that an increase in GLI2 expression also correlated with a decrease in the expression of E-cadherin and an increase in vimentin [74] .…”
Section: Gli2 and Disease: Congenital Malformations And Cancermentioning
confidence: 99%
“…It is part of the final step in the pathway that is regulated by the zinc finger transcription factors, Gli1 and Gli2, which are activators of the Hh target genes. It has also been demonstrated that a high expression of Gli1 by immunohistochemistry is an independent risk factor for skip metastasis of axillary lymph nodes in breast cancer [49][50]. The study by Zhang demonstrate that activation of the Hh pathway signified by increased expression of Gli1 does seem to have a correlation with both the development of disease and its aggressiveness, which makes this pathway a potential target for future therapy [50].…”
Section: Discussionmentioning
confidence: 93%
“…It has also been demonstrated that a high expression of Gli1 by immunohistochemistry is an independent risk factor for skip metastasis of axillary lymph nodes in breast cancer [49][50]. The study by Zhang demonstrate that activation of the Hh pathway signified by increased expression of Gli1 does seem to have a correlation with both the development of disease and its aggressiveness, which makes this pathway a potential target for future therapy [50]. In our study, we found that SMO and Gli1 expressions were significantly reduced by Sal treatment in a dose-dependent manner using western blotting and RT-PCR.…”
Section: Discussionmentioning
confidence: 98%